Association of bud and anther morphology with developmental stages of the male gametophyte of melon (Cucumis melo L.) - M. L. Nguyen; T.N.B.T. Huyen; D. M. Trinh; A. V. Voronina (Вавиловский журнал генетики и селекции)
Correlations between the morphological features of f lower buds and the developmental stages of the male gametophyte are of great practical interest as a reliable marker that accelerates and simplif ies the selection of appropriate plant material for isolated microspore culture. Microspore culture enables one to quickly obtain many pure lines of different vegetable crops, but it has not yet been widely applied in the melon (Cucumis melo L.). To successfully apply this technique in a new culture, one has to optimize many of its elements: f irst, f ind the biological markers for selecting the f lower buds containing the microspores of certain development stages. The paper presents the results of research estimating the correlations between the length and diameter of the f lower buds, the length of the visual part of the corolla, the length of the anthers and the development stages of the male gametophyte in the F1 hybrid of the Kim Hong Ngoc melon. The strongest correlation (CC = 0.885) was found for the f lower bed diameter and a strong correlation (CC = 0.880), for the bud length. The corolla’s visual part was a less reliable morphological feature, and the anther’s length should not be used as a parameter to predict the developmental stages of the melon’s male gametophyte. It was also found that one anther could contain the microspores and pollen grains of different developmental stages. In the f lower buds less than 4 mm in length and 1.51 ± 0.02 mm in diameter prevailed tetrads, and in the buds 4.0–4.9 mm in length and 2.30 ± 0.02 mm in diameter, early microspores. The microspores of a middle stage of development prevailed in the f lower buds 5.0–5.9 mm in length and 2.32 ± 0.00 mm in diameter; mid and late vacuolated microspores, in the buds 6.0–8.9 mm in length and 2.96 ± 0.37 mm in diameter; and two-celled pollen, in the buds more than 9 mm in length and more than 3.97 ± 0.34 mm in diameter.